PROFESIONALISME GURU DALAM MENINGKATKAN PRESTASI SISWA PADA MADRASAH TSANAWIYAH DI KECAMATAN DUAMPANUA KABUPATEN PINRANG - Samonding, Samonding (UIN Alauddin Makassar, 2015)
Abstract: The aim of this study were 1) to find out the level of teachersâ professionalism in MTs at Duampanua District, Pinrang Regency, 2) to find out the level of student achievement in MTs at Duampanua disctict, Pinrang Regency. 3)Â to find out the effect of teachersâ professionalism toward student achievement in MTs at Duampanua Distict, Pinrang Regency. This research was descriptive quantitative, with ex post facto design. The location of this research was MTs atÂ Duampanua District, Pinrang Regency. The population of this research was the headmaster, teachers, students, parents, and other elements in all MTs atÂ Duampanua district, Pinrang regency, with a sample of 25% of the total population. The data collection methods were observation, interviews, questionnaires, and documentation. The technique of data analysis was the quantitative using percentage. The results of the research showed that teacher professionalism was good in both aspects quality and quantity. Student achievement was classified high category. The effect of teachersâ professionalism toward the increasing of student achievementÂ measured by the six aspects was in the high category.Abstrak: Penelitian ini bertujuan; 1) mengetahui tingkat profesionalisme guru pada MadÂraÂsah Tsanawiyah di kecamatan Duampanua kabupaten Pinrang. 2) mengetahui tingkat prestasi siswa pada Madrasah Tsanawiyah di kecamatan Duampanua kaÂbupaten Pinrang. 3) mengetahui tingkat profesionalisme guru pengaruhnya terÂhaÂdap prestasi belajar siswa pada Madrasah Tsanawiyah di Kecamatan DuamÂpaÂnua Kabupaten Pinrang. Penelitian ini bersifat deskriptif kuantitatif dengan jenis penilitian Ex Post Facto. Lokasi penelitian ini adalah Madrasah Tsanawiyah di wiÂlayah Kecamatan Duampanua Kabupaten Pinrang. Populasi dari penelitian ini adaÂlah kepala madrasah, guru, siswa, orang tua, dan unsur lainnya dalam lingÂkup Madrasah Tsanawiyah se Kecamatan Duampanua Kabupaten Pinrang, deÂngan sampel 25% dari jumlah populasi. Metode pengumpulan data yang diguÂnaÂkan adalah; observasi, wawancara, angket, dan dokumentasi. Teknik analisis data adalah persentase kuantitatif. Hasil penelitian menunjukkan profesionalisme guÂru cukup memadai baik dari aspek kualitas maupun kuantitasnya. Prestasi belaÂjar siswa tergolong dalam kategori Â tinggi. Pengaruh profesionalisme guru terhadap peÂningkatan prestasi belajar siswa yang diukur dengan enam aspek masuk dalam kaÂtegori tinggi.